As vozes das mulheres da EJA: um olhar voltado para a inserção no ensino superior - Rocha, Brenda Generoso de Lima (Universidade Federal de São Carlos, 2022)
This master's research aimed to analyze the narratives of three women who graduated from EJA (Portuguese acronym for Youth and Adult Education) and what were the transforming elements and the excluding elements that influenced the insertion of these women in higher education, having Dialogical Learning (1997) as a theoretical-methodological foundation, based on some central authors such as Flecha (1997); Freire (1985; 1997; 2005; 2009; 2011; 2014), following the dual perspective described by Giddens (1991; 1996; 2003). This is a qualitative field research based on twelve narratives of three women who graduated from EJA, who have already concluded higher education in Pedagogy in Brazilian federal public institutions. Due to the Covid-19 pandemic, the narratives were virtually collected based on the Life Stories methodology guidelines (JOSSO, 2004) and analyzed based on the contributions of the Communicative Methodology (GÓMEZ et al, 2006). The narratives present excluding elements and transforming elements, both in the school trajectory and in the social environment of the three women with regard to influences in the their journey towards a higher education degree. As excluding elements, the data revealed the denial of the right of access to and permanence in school spaces, the presence of male chauvinism as a consequence of men's domination over women and the female role in the patriarchal and capitalist society in which we live. As transforming elements, the data put in evidence the instrumental dimensions, such as a gain in autonomy and critical thinking, highlighting the role of the progressive teacher (FREIRE, 2009), in addition to solidary relationships in building support networks for women. It is expected that those discussions contribute towards the role of this progressive teacher and solidary relationships in the fight against male chauvinism and ageism, helping with new public policies for this modality of education, which is marked by a historical context of exclusion and a current situation that still needs transforming instruments so that new EJA graduates are also included in the university environment, as a right.
EJA's women voices: a perspective towards higher education inclusion
Keywords: Educação de Jovens e Adultos; Mulher; Egresso; Ensino superior; Youth and Adult Education; High school graduate; Women; Higher education; CIENCIAS HUMANAS::EDUCACAO